Industry in Tanzania: Performance, prospects, and public policy - John M. Page (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Tanzania ranks among the leading stars of the 'African growth miracle', but a sector that has been largely absent from the Tanzania success story is industry. Although growth of manufacturing has outpaced economic growth over the past decade, relative to international norms and its ambitious plans to achieve middle-income status Tanzania suffers from a 'manufacturing deficit' at its current level of per capita income. The paper discusses a number of policy initiatives that should be undertaken to strengthen the industrial sector's recent dynamism, including strengthening Special Economic Zones, improving trade logistics, and reforming Micro and Small Enterprise programmes.
Keywords: O14; O25; O55; 330; Tanzania; industrial development; industrial policy; structural transformation